Measuring the Impact of Synthetic Phonics Teaching on the Acquisition of Upper and Lowercase Recognition Skills: Evidence from Oman - Noora Al-Sukaiti (Research Highlights in Language, Literature and Education Vol. 4, 2023)
Letter name knowledge is regarded as one of the most significant indicators of later reading ability, and a poorly established alphabetic knowledge is a well-known predictor of future reading difficulties. Alphabet knowledge encompasses recognition of the alphabet, identifying the names and sounds of letters, and producing letters. This chapter aims to assess the impact of a synthetic approach to phonics on Omani third graders’ acquisition of uppercase (UC) and lowercase (LC) recognition. The study included 117 Omani male and female third graders in two schools in Al-Dhahira Governorate in the Sultanate of Oman during the academic year 2019/2020. A quantitative descriptive research design was used in the study, and data was collected using a UC and LC letter recognition test. According to the findings, 43.6% of third graders in this study’s sample were below the minimum required level, while the remaining 56.4% were at or above the minimum required level. Furthermore, there was a statistically significant difference in third graders’ UC letter recognition and LC recognition scores in favor of UC letters. The study showed with a set of recommendations for the ministry and English teachers in order to improve the delivery of synthetic phonics teaching as a literacy-enhancing approach in the Omani context. The study is notable since it is the first to examine the effect of synthetic phonics instruction on the development of upper- and lowercase recognition skills among Omani third graders.